Perkawinan Campuran Di Indonesia Ditinjau Dari Hukum Islam Dan Hukum Positif - Defanti Putri Utami; Finza Khasif Ghifarani (MASADIR: Jurnal Hukum Islam, 2021)
Marriage is an inner and outer bond between a man and a woman in forming a sakinah mawaddah warahmah family. In the study of Islamic law studies in Indonesia, there is a discussion about mixed marriages. In the classical fiqh understanding, when faced with the term mixed marriage, the paradigm that emerges is interfaith marriage. Along with the development of the times and technology at this time, mixed marriages are not only limited to religious differences, further than that there are also mixed marriages due to differences in citizenship. Furthermore, this paper will discuss further about mixed marriages in Indonesia from the perspective of Islamic law and positive law with all the problems that arise as a result of mixed marriages.